2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--21640
|View full text |Cite
|
Sign up to set email alerts
|

Learning MATLAB in the Inverted Classroom

Abstract: University courses have retained the same basic structure for hundreds of years. That structure follows an easily identifiable work flow: 1. Students come to a class meeting during which a lecture is given. Students take notes and occasionally ask questions. 2. Following the lecture, learners are assigned work to be completed outside of class. This usually takes the form of homework, test preparation, or writing papers. 3. The outside-of-class work is submitted or assessed in class. The cycle then repeats. Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
13

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 7 publications
2
44
0
13
Order By: Relevance
“…Providing students with a relaxed non-threatening learning environment and friendly atmosphere through which they were motivated to participate in all tasks. This is consistent with Talbert (2012) and Kim, et.al. (2014) who stressed the importance of providing a welcoming and caring learning environment as one of the main principles for designing effective flipped classroom.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…Providing students with a relaxed non-threatening learning environment and friendly atmosphere through which they were motivated to participate in all tasks. This is consistent with Talbert (2012) and Kim, et.al. (2014) who stressed the importance of providing a welcoming and caring learning environment as one of the main principles for designing effective flipped classroom.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…2012 was a watershed year for flipped learning (Bergmann and Sams 2012;Bond 2020;Talbert 2012Talbert , 2017 as this was the point at which it began to be used as an active pedagogy as well as becoming the subject of academic research. Having examined the databases for the publications between 2000 and 2012 (e.g.…”
Section: The Rationale For a Comprehensive Review Of Studies On The Fmentioning
confidence: 99%
“…In addition, it was concluded that the preparatory nature of the home tasks to the class tasks made it easier for the students to do the class tasks, to learn words and make sentences, and that the home tasks were useful before exams. In the literature, there are studies indicating that the studies conducted at home in the flipped learning model are disadvantageous for this model (Sırakaya, 2017;Turan & Göktaş, 2015), and there are also studies indicating that the studies conducted at home increase the active participation and success of the students (Arslan & Kuzu, 2019;Talbert, 2012). The fact that this study was carried out with the action research method and changes made according to the needs and opinions of the students in the process may have provided the students' views on this subject to be positive.…”
Section: Second Research Questionmentioning
confidence: 99%